Increased Frequencies of Switched Memory B Cells and Plasmablasts in Peripheral Blood from Patients with ANCA-Associated Vasculitis - Evelina Elmér; Sofia Smargianaki; Åsa Pettersson; Lillemor Skattum; Sophie Ohlsson; Thomas Hellmark; Åsa C. M. Johansson (Journal of Immunology Research)
B cells are thought to play a central role in the pathogenesis of antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV). ANCAs have been proposed to cause vasculitis by activating primed neutrophils to damage small blood vessels. We studied a cohort of AAV patients of which a majority were in remission and diagnosed with granulomatosis with polyangiitis (GPA). Using flow cytometry, the frequencies of CD19+ B cells and subsets in peripheral blood from 106 patients with AAV and 134 healthy controls were assessed. B cells were divided into naive, preswitch memory, switched memory, and exhausted memory cells. Naive and switched memory cells were further subdivided into transitional cells and plasmablasts, respectively. In addition, serum concentrations of immunoglobulin A, G, and M were measured and clinical data were retrieved. AAV patients displayed, in relation to healthy controls, a decreased frequency of B cells of lymphocytes (5.1% vs. 8.3%) and total B cell number. For the subsets, a decrease in percentage of transitional B cells (0.7% vs. 4.4%) and expansions of switched memory B cells (22.3% vs. 16.5%) and plasmablasts (0.9% vs. 0.3%) were seen. A higher proportion of B cells was activated (CD95+) in patients (20.6% vs. 10.3%), and immunoglobulin levels were largely unaltered. No differences in B cell frequencies between patients in active disease and remission were observed. Patients in remission with a tendency to relapse had, compared to nonrelapsing patients, decreased frequencies of B cells (3.5% vs. 6.5%) and transitional B cells (0.1% vs. 1.1%) and an increased frequency of activated exhausted memory B cells (30.8% vs. 22.3%). AAV patients exhibit specific changes in frequencies of CD19+ B cells and their subsets in peripheral blood. These alterations could contribute to the autoantibody-driven inflammatory process in AAV.